The ruby airship - Gosling, Sharon (North Mankato, Minnesota Switch Press, a Capstone imprint, 2015)
Rémy Brunel, acrobat and former jewel thief, stayed behind in London when the circus left, but she is starting to feel lonely, so when magician Yannick, an old friend, turns up she decides to return to France and the circus with him--but detective Thaddeus Rec believes Yannick is up to no good, and determines to pursue them in an airship to win her back
"First published in 2013 by Curious Fox, an imprint of Capstone Global Library Limited."
English stories
Sequel to: The diamond thief
Sequel: The sapphire cutlass
1 2 13 15
Keywords: Airships -- Juvenile fiction; Circus performers -- Juvenile fiction; Detective and mystery stories; Jewel thieves -- Juvenile fiction; Magicians -- Juvenile fiction; Police -- England -- London -- Juvenile fiction; Acrobats -- Fiction; Airships -- Fiction; Magicians -- Fiction; Mystery and detective stories; Police -- Fiction; Robbers and outlaws -- Fiction; London (England) -- History -- 19th century -- Juvenile fiction; Paris (France) -- History -- 19th century -- Juvenile fiction; France -- History -- 19th century -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction; London (England) -- History -- 19th century -- Fiction; Paris (France) -- History -- 19th century -- Fiction; Adventure fiction; Mystery fiction